Daydreaming factories. Issue 2 (2022) - Nassehi, Aydin; Colledani, Marcello; Kádár, Botond; Lutters, Eric
Abstract: Optimisation of factories, a cornerstone of production engineering for the past half century, relies on formulating the challenges with limited degrees of freedom. In this paper, technological advances are reviewed to propose a "daydreaming" framework for factories that use their cognitive capacity for looking into the future or "foresighting". Assessing and learning from the possible eventualities enable breakthroughs with many degrees of freedom and make daydreaming factories antifragile. In these factories with augmented and reciprocal learning and foresighting processes, revolutionary reactions to external and internal stimuli are unnecessary and industrial co-evolution of people, processes and products will replace industrial revolutions.